Compliance with International Standards on Auditing (ISAs): Evidence from Kosovo for the Financial Reporting Period 2015–2019 - A. H. Hoti; L. S. Sopa (Финансы: теория и практика, 2022)
The aim of this empirical study is to determine the compliance of the audit reports of the financial statements of large companies in Kosovo for 2015–2019 with the requirements of the International Standards on Auditing (ISA). The relevance of the study is due to the fact that many countries are now actively moving to the application of the International Standards on Auditing while feeling the lack of detailed methodological materials, which makes it difficult to effectively apply these standards in countries that do not have experience in this area. The basis for the study is a random sample of published audit reports of large companies in Kosovo, about 37% of the total population, which can be considered sufficient. The authors analyze the misstatements (errors) made by the auditors of domestic audit firms in Kosovo when preparing audit reports on the financial statements of large companies in Kosovo in 2015–2019. Based on the analysis, the authors conclude that the quality of the audit in Kosovo is insufficient. The level of non-compliance with ISAs remains high, and licensed auditors and audit firms are not adequately trained to satisfactorily fulfill their legal obligations. The results of this study have implications for national audit regulatory bodies (ARBs) and professional accountancy organizations (PAOs) that want to improve overall audit quality.